Youth Farmer’s Training : Business Model for Scaling Happy Seeder Technology - Jat, Mangi Lal; Bijarniya, Deepak; Kalvaniya, Kailash C.; Choudhary, Kajod Mal; Kumar, Yogesh; Rana, Dharamvir Singh (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Rural youth continue to face challenges related to unemployment, underemployment and poverty. Despite the agricultural sector’s ample potential to provide income-generating opportunities for rural youth, challenges related specifically to youth participation in this sector and more importantly options for overcoming them are not extensively documented. For youth to successfully participate in the agricultural sector, access to both information and education are crucial. In addition to knowledge of agricultural production and processing techniques and the relative know-how, young farmers need access to information about finance, land and markets.The training strongly emphasized participatory extension principles and entrepreneurship as means of increasing farm productivity amongst young farmers. Utilizing field mechanization as a means of optimizing the number of youth engaged in face-to-face learning, past workshops were held for young farmers that served to provide space for interactions with experts, discuss methods for improving delivery of services, and learn a new component of agribusiness and entrepreneurship with the intent of transferring this information to more youth farmers in a similar way.